TANGGUNG JAWAB PELAKU USAHA PARKIR TERHADAP KEHILANGAN KENDARAAN KONSUMEN BERDASARKAN HUKUM POSITIF INDONESIA - Dertina Basar T Simanjuntak; Arista Candra Irawati (Fakultas Hukum Universitas 17 Agustus (UNTAG) Semarang, 2026)
Abstract The responsibility of parking operators for the loss of motorcycles is an increasingly relevant issue in the context of consumer protection in Indonesia. This research aims to explore consumer rights and the obligations of parking operators in maintaining the security of parked vehicles. Three main issues addressed in this study are: (1) What is the legal responsibility of parking operators in maintaining the security of consumers vehicles? (2) How do consumers perceive the effectiveness of the security measures implemented by parking operators?. The approaches used in this research include the statute approach and the conceptual approach. The research results show that consumers receive legal compensation. Consumers also expressed dissatisfaction with the response of parking management in the event of a loss, as they are required to provide proof of parking ticket and proof of ownership of the lost motorcycle or car. The data obtained were analyzed thematically to identify patterns and perspectives emerging from consumer experiences. The findings indicate that many consumers feel dissatisfied with the level of security provided and the lack of transparency regarding security procedures. Consumers also expressed dissatisfaction with the response of parking operators when a loss occurred. By referring to existing regulations, including Law No. 8 of 1999 concerning Consumer Protection, this study recommends the implementation of better security measures and improved communication between parking managers and consumers. These findings are expected to contribute to the development of more effective policies in the context of consumer protection in the parking sector, thereby minimizing the risk of vehicle loss in the future.